PROPOSED MARKETING STRATEGY FOR GREEN BUSINESS IN BANDUNG (CASE STUDY: BIYA PROJECT) - Qinanti, Rizqyani; Wandebori, Harimukti (Jurnal Apresiasi Ekonomi, 2023)
This research study delves into the development of a marketing strategy for the Biya Project, an environmentally conscious enterprise in Bandung, Indonesia. The study employs various strategic analysis tools and frameworks, including the business model canvas, value proposition canvas, SWOT analysis, TOWS matrix, also competitor environment analysis. The research methodology involved data collection through surveys, interviews, and secondary sources, with a focus on consumer analysis, segmentation, targeting, and positioning strategies. The study also encompassed an external analysis, considering political, legal, economic, demographic, sociocultural, technical, global, and physical factors, to identify opportunities and threats for the Biya Project. The findings revealed that the project faced challenges such as financial constraints and high competition, but also benefited from government support for recycling plastic waste and a growing demand for sustainable products. The study proposed strategies to leverage branding for sustainable products, target Generation Z, and implement crisis communication strategies using the TOWS matrix. The research also highlighted the favorable regulatory environment for environmentally friendly firms in Bandung, economic conditions influencing consumer behavior, and the competitive landscape in the plastic recycling industry. The Biya Project strategically positioned its brand to counter threats and promote supply chain transparency, leveraging its strengths and addressing weaknesses to enhance its business model and value proposition. The study concludes with an ongoing marketing strategy, workforce development initiatives, and an implementation plan to address the company's financial and operational capabilities as a green business. This research provides valuable insights for environmentally conscious enterprises seeking to develop effective marketing strategies and navigate the business environment in similar contexts.